High current heavy ion beam investigations at GSI-UNILAC. Issue 1 (1st January 2023) - Vormann, H; Barth, W; Miski-Oglu, M; Scheeler, U; Vossberg, M; Yaramyshev, S
Abstract: The GSI Universal Linear Accelerator UNILAC and the synchrotron SIS18 will serve as injector for the upcoming FAIR-facility. The UNILAC-High Current Injector will be improved and modernized until FAIR is commissioned and the Alvarez post stripper accelerator is replaced. The reference heavy ion for future FAIR-operation is uranium, with highest intensity requirements. To re-establish uranium beam operation and to improve high current beam operation, different subjects have been explored in dedicated machine investigation campaigns. After a beam line modification in 2017 the RFQ-performance had deteriorated significantly; new rods have been installed and the RF-working point has been redefined. Also the Superlens-performance had become unsatisfactory; improved with a modified RF-coupler. With a pulsed hydrogen gas stripper target the uranium beam stripping efficiency could be increased by 65%. Various work has already been carried out to establish this stripper device in routine operation. With medium heavy ion beams a very high beam brilliance at the end of transfer line to SIS18 was achieved. Results of the measurement campaigns and the UNILAC upgrade activities will be presented.